(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: A common response to stress is anxiety which present in patient undergoing c -section surgery as compared to general surgical population. the primary aim of this study was to investigate pre-operative anxiety in patient who were undergoing for C-section surgery at tertiary care hospital in Peshawar Pakistan Objective: The study’s main goal was to look into pre-operative anxiety in patients having C-section surgeries in a tertiary care facility in Peshawar, Pakistan. Methodology: An institutional base cross-sectional study was conducted from July 2023 to September 2023 with total of 100 patients who undergoing for C-section surgery were included and STAI Was the study tool use for assess pre –operative anxiety in patient who were undergoing for C-section surgery. Results: The overall pre-operative anxiety rate was respectively (13,9,78%) mild, moderate, and sever. but the study’s findings indicated that patients undergoing for C section surgery had a high anxiety rate of (78%), Additionally, the looked at the significant relationships between anxiety age, and gravida, as well as between STATE and TRAIT anxiety. According to the results of the chi-square test, there was a positive relationship between anxiety TRAIT and gravida Conclusion: Study discovered that the participant average anxiety levels were measured at 78%. The high rate of pre-operative anxiety shown in this study emphasizes how important it is for healthcare professional to identify and treat this problem in order to improve the overall surgical experience and patient outcome.